Social Psychological Factors Influencing Probiotic Yogurt Consumption of Female Millennials - Sayruamyat, Suwanna; Pornchanarak , hart; Premashthira, Aerwadee (Business Administration and Management Journal Review, 2023)
This article aims to study the female millennial behavior of probiotic yogurt consumption and estimate the impact of psychological factors on probiotic yogurt consumption of female millennials in Bangkok and metropolitan region. The analysis applies the theory of planned behavior and estimates by structural equation modeling. 266 female millennials were collected during March to April 2020. The result demonstrates that respondents only perceived behavioral control has positively impact on intention and indirectly impact on probiotic yogurt consumption. This research suggests that yogurt entrepreneurs should do marketing campaign focusing female millennial through convenience stores and promote health benefits of regularly yogurt consumption.